Hydrogen as a long-term, large-scale energy storage solution when coupled with renewable energy sources or grids with dynamic electricity pricing schemes. (24th June 2020) - Mayyas, Ahmad; Wei, Max; Levis, Gregorio
Abstract: One of the key challenges that still facing the adoption of renewable energy systems is having a powerful energy storage system (ESS) that can store energy at peak production periods and return it back when the demand exceeds the supply. In this paper, we discuss the costs associated with storing excess energy from power grids in the form of hydrogen using proton exchange membrane (PEM) reversible fuel cells (RFC). The PEM-RFC system is designed to have dual functions: (1) to use electricity from the wholesale electricity market when the wholesale price reaches low competitive values, use it to produce hydrogen and then convert it back to electricity when the prices are competitive, and (2) to produce hydrogen at low costs to be used in other applications such as a fuel for fuel cell electric vehicles. The main goal of the model is to minimize the levelized cost of energy storage (LCOS), thus the LCOS is used as the key measure for evaluating this economic point. LCOS in many regions in United States can reach competitive costs, for example lowest LCOS can reach 16.4¢/kWh in Illinois (MISO trading hub) when the threshold wholesale electricity price is set at 25/MWh, and 19.9¢/kWh in Texas (ERCOT trading hub) at threshold price of 20/MWh. Similarly, the levelized cost of hydrogen production shows that hydrogen can be produced at very competitive costs, for example the levelized cost of hydrogen production can reach 2.54/kg-H2 when using electricity from MISO hub. This value is close to the target set by the U.S. Department of Energy. Graphical abstract: Levelized cost of energy storage (LCOS) curves for several regions in the United States. Image 1 Highlights: A model to calculate the levelized cost of energy storage for reversible fuel cells. RFC system as energy storage system can increase the resiliency of the power grids. RFC can be designed to store electricity and produce hydrogen for other uses. Roundtrip efficiency and capital cost are key factors that shape the LCOS in RFC.